An investigation of presynaptic alpha-adrenoceptor subtypes in the pithed rat heart and in the rat isolated vas deferens. - Docherty, J. R. (Nature Publishing Group, 1984)
The presynaptic cardio-inhibitory effects of the alpha-adrenoceptor agonists xylazine, cirazoline and amidephrine and their interaction with the antagonists yohimbine and prazosin were investigated in the pithed rat. The presynaptic inhibitory effects of the alpha 2-selective agonist xylazine were antagonized by the alpha 2-antagonist yohimbine but not by the alpha 1-antagonist prazosin, thus demonstrating the lack of alpha 2-adrenoceptor antagonism by prazosin. The presynaptic inhibitory effects of cirazoline were antagonized equally by yohimbine and prazosin, and the presynaptic inhibitory effects of the selective alpha 1-agonist amidephrine were antagonized by prazosin more potently than by yohimbine. In the nifedipine-treated isolated epididymal portion of the rat vas deferens, both xylazine and amidephrine produced concentration-dependent inhibition of the isometric contraction to single pulse electrical stimulation. The alpha 2-antagonist rauwolscine antagonized the inhibitory effects of xylazine but not of amidephrine . It is concluded that inhibitory alpha 1-adrenoceptors, as well as the already established alpha 2-receptors, are present presynaptically in the pithed rat heart and in the rat vas deferens.